Islamic design : a mathematical approach - Wichmann, Brian ; Wade, David (Birkhäuser, 2020)
This book deals with the genre of geometric design in the Islamic sphere. Part I presents an overview of Islamic history, its extraordinary spread from the Atlantic to the borders of China in its first century, its adoption of the cultural outlook of the older civilisations that it conquered (in the Middle East, Persia and Central Asia), including their philosophical and scientific achievements - from which it came to express its own unique and highly distinctive artistic and architectural forms. Part II represents the mathematical analysis of Islamic geometric designs. The presentation offers unlimited precision that allows software to reconstruct the design vision of the original artist. This book will be of interest to Islamic academics, mathematicians as well as to artists and art students. Foreword.- I Cultural Context.- 1 A History.- 2 The Scientific Contribution.- 3 Religious Dimension.- 4 The Evolution of Style.- 5 Materials and Mediums.- 6 Countries and Regions.- II Mathematical Analysis.- 7 Introduction.- 8 A Worked Example.- 9 An Octagonal Set.- 10 Octagonal Tiles with a Large Star.- 11 Lines and Edges.- 12 Decagonal Patterns.- 13 What Is Correct?.- 14 6-fold Delights.- 15 Two Level Patterns.- 16 Two Mamluk Masterpieces.- 17 Conclusions.- A The Symmetry of a Tiling.- B Key Dates.- C Glossary.- D Copyright.